2011
DOI: 10.1007/s12565-011-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of myostatin, follistatin and decorin expression in muscle of different origin

Abstract: Muscle regeneration supports muscle function in aging, and plays a role in the functional impairment caused by progressive neuromuscular diseases. Major substances controlling this process are growth factors and the extracellular matrix (ECM). Thus, follistatin is known to antagonize the function of several members of the TGF-β family of secreted signaling factors, including myostatin-the most powerful inhibitor of muscle growth characterized to date. Decorin-a small leucine-rich proteoglycan-traps myostatin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…For example, Dlk1, which is both a Wnt target gene and a Notch ligand, controls postnatal muscle growth and its ablation in the myogenic lineage results in postnatal growth retardation, reduced body and muscle weight, and impaired regeneration ; a phenotype that resembles that of Barx2 null mice. Fst is another Wnt target critical for muscle growth and regeneration . Notch3, which was elevated in Barx2−/− myoblasts, is suggested to be an inhibitor of satellite cell proliferation and self‐renewal via inhibition of Notch1 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dlk1, which is both a Wnt target gene and a Notch ligand, controls postnatal muscle growth and its ablation in the myogenic lineage results in postnatal growth retardation, reduced body and muscle weight, and impaired regeneration ; a phenotype that resembles that of Barx2 null mice. Fst is another Wnt target critical for muscle growth and regeneration . Notch3, which was elevated in Barx2−/− myoblasts, is suggested to be an inhibitor of satellite cell proliferation and self‐renewal via inhibition of Notch1 .…”
Section: Discussionmentioning
confidence: 99%
“…The results in this study showed that expression of MSTN was inhibited, which was similar with the results of in vivo study, supporting FST still worked on myoblasts. DCN, a out‐cellular ligand of TGFβpathway, also a competitor of FST (Hiroki et al., ), and its expression didn't show obvious changes. Expression of ACVR1 and ACVR2 in duck's myoblasts did not change when treated with FST suggesting it cannot regulate expression of ACVR1 and ACVR2.…”
Section: Discussionmentioning
confidence: 99%
“…They found that not only inhibition of MSTN, but also of activin (ACT) and proliferation of satellite cells are involved in follistatin-induced muscle hypertrophy [12]. Follistatin thus might offer a novel therapeutic strategy for muscular injuries and dystrophy by suppressing the progression of muscle degeneration and permitting skeletal muscle mass restoration [15]. However, before translating follistatin-based therapies from the bench to the bedside, clear mechanisms of how follistatin promotes muscle regeneration require extensive investigation.…”
Section: Recombinant Proteins In Muscle Regenerationmentioning
confidence: 99%